2020
DOI: 10.1111/ijlh.13314
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein‐induced activated partial thromboplastin time prolongation in heparinized samples is attenuated by elevated factor VIII

Abstract: Introduction Activated partial thromboplastin time (aPTT) and antifactor Xa (anti‐Xa) activity are used to monitor unfractionated heparin therapy in children on extracorporeal membrane oxygenation (ECMO). Elevated C‐reactive protein (CRP) can prolong aPTT and cause discrepancy between these two assays. We aimed to evaluate CRP effect on aPTT and anti‐Xa assays in the presence of heparin and to determine whether elevated CRP affects laboratory monitoring in pediatric ECMO patients. Materials and methods Citrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Heparinase-treated aPTT (HPTT) helps to eliminate the heparin effect and reveal the underlying coagulable state, yet HPTT is still rarely used in most institutions due to its cost. It is also important to note that phospholipid-binding proteins such as lupus anticoagulant and C-reactive protein (CRP) may also prolong aPTT and HPTT ( 7 , 28 ) and this effect must be considered when assessing aPTT and anti-Xa in gaging anticoagulation with heparin.…”
Section: Resultsmentioning
confidence: 99%
“…Heparinase-treated aPTT (HPTT) helps to eliminate the heparin effect and reveal the underlying coagulable state, yet HPTT is still rarely used in most institutions due to its cost. It is also important to note that phospholipid-binding proteins such as lupus anticoagulant and C-reactive protein (CRP) may also prolong aPTT and HPTT ( 7 , 28 ) and this effect must be considered when assessing aPTT and anti-Xa in gaging anticoagulation with heparin.…”
Section: Resultsmentioning
confidence: 99%
“…aPTT and/or anti-Xa are most commonly used to assess adequate UFH-related anticoagulation given that ACT is unreliable in the pediatric ECMO setting and viscoelastic testing is not broadly available (11)(12)(13)(14). However, aPTT is effected by other factors such as presence of lupus anticoagulant, elevated C reactive protein, and increased factor VIII level (15)(16)(17)(18). Anti-Xa assays use platelet-poor-plasma (PPP) and are not functional clot time-based tests as they do not account for thrombin, fibrinogen, and other blood cells, which contribute to coagulation.…”
mentioning
confidence: 99%
“…APTT readings may be falsely shortened in patients receiving UFH with an elevated C‐reactive protein, dependent upon the chosen assay or high FVIII levels 49 . Anti‐Xa monitoring may therefore be preferable in these patients, which is of relevance to a significant proportion of COVID‐19 patients 50 . A pre‐COVID study of 539 hospitalized patients receiving UFH found that patients with disproportionately prolonged APTT readings compared with anti‐Xa values had worse clinical outcomes.…”
Section: Can Anti‐xa Be Helpful To “Detecting” Heparin Resistance?mentioning
confidence: 99%
“… 49 Anti‐Xa monitoring may therefore be preferable in these patients, which is of relevance to a significant proportion of COVID‐19 patients. 50 A pre‐COVID study of 539 hospitalized patients receiving UFH found that patients with disproportionately prolonged APTT readings compared with anti‐Xa values had worse clinical outcomes. The authors suggested that concurrent measurement of both readings could be useful in stratifying bleeding risk and determining dose.…”
Section: Can Anti‐xa Be Helpful To “Detecting” Heparin Resistance?mentioning
confidence: 99%